2018
DOI: 10.1111/een.12659
|View full text |Cite
|
Sign up to set email alerts
|

Predator and floral traits change pollinator behaviour, with consequences for plant fitness

Abstract: 1. Flower-dwelling predators may interfere in plant-pollinator interactions through changes in pollinator behaviour, leading to a reduction in pollination services. Although the context-dependency of tri-trophic interactions is often acknowledged, the relative contribution of predator, pollinator and flower traits in shaping pollinator behaviour has been rarely studied simultaneously.2. Pollinators' responses to predation risk were evaluated using artificial spiders on Alstroemeria aurea flowers in order to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The larger spider models were made to determine whether pollinators perceived and respond to larger objects as a greater predation risk, since preliminary field observations suggested that real spiders were often not detected by pollinators. However, this is possibly due to spider hunting strategies such as background colour matching (i.e., body colour similar to the background colour) or behavioural strategies such as remaining still and hiding within flowers, either between petals or below stamens (Gavini et al, ). Yet, bumblebee corpses are found in the field, indicating that they are subject to some level of predation risk.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The larger spider models were made to determine whether pollinators perceived and respond to larger objects as a greater predation risk, since preliminary field observations suggested that real spiders were often not detected by pollinators. However, this is possibly due to spider hunting strategies such as background colour matching (i.e., body colour similar to the background colour) or behavioural strategies such as remaining still and hiding within flowers, either between petals or below stamens (Gavini et al, ). Yet, bumblebee corpses are found in the field, indicating that they are subject to some level of predation risk.…”
Section: Methodsmentioning
confidence: 99%
“…Pollinator traits such as body size, taxon and sociality are crucial traits for explaining the differences in pollinator behaviour in the presence of predators (reviewed by Romero et al, ). In turn, pollinator behaviour in response to predation risk is also known to vary due to a combination of traits among all interacting partners (Gavini, Quintero, & Tadey, ; Llandres, Mas, & Rodríguez‐Gironés, ). In particular, specific traits of predators such as colour, size and hunting mode (Bray & Nieh, ; Kersch‐Becker, Grisolia, Campos, & Romero, ; Llandres & Rodríguez‐Gironés, ; Miller, Ament, & Schmitz, ; Wang, Ings, Proulx, & Chittka, ) or plant traits such as reward availability (Abbot, ; Jones, ; Jones & Dornhaus, ; Llandres et al, ) can influence pollinator response to predation risk.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations